Leptospira borgpetersenii serovar Hardjo and Leptospira santarosai serogroup Pyrogenes isolated from bovine dairy herds in Puerto Rico - Hamond, Camila; Dirsmith, Katherine L.; LeCount, Karen; Soltero, Fred V.; Rivera-Garcia, Sarai; Camp, Patrick; Anderson, Tammy; Hicks, Jessica A.; Galloway, Renee; Sutherland, Graham; Schafer, Ilana J.; Goris, Marga G. A.; et al. (Frontiers in Veterinary Science, 2022)
Leptospirosis is one of the most common zoonotic diseases in the world and endemic in the Caribbean Islands. Bovine leptospirosis is an important reproductive disease. Globally, cattle are recognized as a reservoir host for L. borgpetersenii serovar Hardjo, which is transmitted via urine, semen, and uterine discharges, and can result in abortion and poor reproductive performance. The dairy industry in Puerto Rico comprises up to 25% of agriculture-related income and is historically the most financially important agricultural commodity on the island. In this study, we report the isolation of two different pathogenic Leptospira species, from two different serogroups, from urine samples collected from dairy cows in Puerto Rico: L. borgpetersenii serogroup Sejroe serovar Hardjo and L. santarosai serogroup Pyrogenes. Recovered isolates were classified using whole-genome sequencing, serotyping with reference antisera and monoclonal antibodies, and immunoblotting. These results demonstrate that dairy herds in Puerto Rico can be concurrently infected with more than one species and serovar of Leptospira, and that bacterin vaccines and serologic diagnostics should account for this when applying intervention and diagnostic strategies.